High-dose gallium-67 therapy in patients with relapsed acute leukaemia: a feasibility study. - Jonkhoff, A. R. (Nature Publishing Group, 1995)
Gallium-67 (67Ga) accumulates in malignant tissues via the transferrin receptor without need for a monoclonal antibody and emits cytotoxic low-energy electrons. In this study we investigated the feasibility, pharmacokinetics, toxicity and preliminary efficiency of high-dose 67Ga injected intravenously (i.v.) in patients with acute leukaemia not responding to conventional therapy. Twelve doses of 36-105 mCi of Gallium67 citrate were administered as a push injection to eight patients with resistant leukaemia in a pilot study. All five patients with acute myeloid leukaemia (AML) and three patients with acute lymphoblastic leukaemia (ALL) had resistant disease or resistant relapse. No (sub)acute toxicity was observed. Independent of the administered dose, whole-blood radioactivity levels 10 min after administration measured only 1.25 +/- 1.39 microCi ml-1, indicating a large volume of distribution. Urine excretion in the first 24 h ranged from 18% to 51.5% (median 29.5%) of the administered dose. Cellular uptake of 67Ga was less than in previous in vitro studies. Whole-body radiation dose was estimated to be 0.25 +/- 0.03 cGy mCi-1. Red marrow dose was estimated to be between 0.18 +/- 0.02 and 0.97 +/- 0.12 cGy mCi-1. One definite response was observed in an ALL patient with disappearance of skin lesions, normalisation of the enlarged spleen and profound leucopenia. Three other patients showed transient reductions in white blood cell counts without disappearance of blasts from the peripheral blood. We conclude that high-dose i.v. 67Ga can be safely administered but that the uptake of 67Ga in blast cells must increase to make 67Ga therapeutically useful in patients with relapsed leukaemia. IMAGES: